Forschungsvorhaben MGA: Münze und Gesellschaft in Alteuropa - Wigg-Wolf, David (e-Forschungsberichte des DAI, 2023)
MGA considers numismatic material as evidence for social, political, economic and cultural developments in an area stretching from Britain to the Black Sea. The basis is the collection and documentation of coin finds from the study area in the database AFE, which has been specially developed together with DBIS, Goethe University, Frankfurt. AFE is also used by the Polish partner project „Finds of Ancient Coins from Territory Historically Associated with Poland“ at the University of Warsaw. AFE employs the concepts of the Linked Open Data project Nomisma.org, and is thus fully integrated into both external projects such as Online Coins of the Roman Empire (OCRE), and the iDAI resources Gazetteer and Zenon.